Cognitive impairment and treatment outcomes amongst people attending an alcohol intervention service for those aged 50+. Issue 2 (28th May 2021) - Seddon, Jennifer; Wadd, Sarah; Elliott, Lawrie; Madoc-Jones, Iolo
Abstract : Purpose: No studies have evaluated the relationship between cognitive impairment and alcohol treatment outcomes amongst older drinkers. This study aims to explore the extent of cognitive impairment amongst older adults seeking alcohol treatment and examine the relationship between cognitive impairment, treatment retention and alcohol use following treatment. Design/methodology/approach: The study used data from the Drink Wise Age Well programme; an alcohol intervention service for older adults (aged 50+). The Montreal Cognitive Assessment was used to screen for cognitive impairment; alcohol use was assessed using the alcohol use disorders identification test. Findings: In total, 531 participants completed the assessment at treatment entry. Over half the sample were male (57%), with a mean age of 60 years (Standard deviation: 7.09). Almost half (48.4%) had cognitive impairment at the entry to treatment: 51.6% had a normal cognitive function, 41.4% had mild cognitive impairment, 5.8% had moderate cognitive impairment and 1.1% had severe cognitive impairment. Cognitive impairment was not associated with increased treatment drop-out and was not predictive of alcohol use following treatment. Alcohol treatment was associated with a significant improvement in cognitive functioning. Originality/value: This study suggests there may be a significant amount of unidentified cognitive impairment amongst older adults attending alcohol treatment. Assessment and routine screening for cognitive impairment in drug and alcohol services may help in care planning and setting treatment goals; in the absence of routine screening opportunities for treatment planning and intervention may be missed.